Design Research in the Digital Era Opportunities and implications. Notes on Doctoral Research in Design 2020 - Rampino, Lucia; Mariani, Ilaria (Design International - Open access, 2020)
This book proposes an overview of the researches initiated in 2015 in the Design PhD programme of Politecnico di Milano. All of them explore the implications of the ongoing digital transformations, from the specific perspective of design research. Throughout the book, the cultural, organisational, social, and managerial issues raised by digital technology, are debated and how such issues call for a reframing of design processes, practices and models.